Mathematics education and use of mathematical language in enhancing understanding of mathematics in secondary schools. - Onderi, Henry; Malala, Getrude; Okelo, Benard O. (Mathematics education and use of mathematical language in enhancing understanding of mathematics in secondary schools., 2012)
There are many factors attributed to the poor performance of mathematics at high school level, for example, students‟ attitude to mathematics, low cognitive abilities, poor teacher-student relationships, poor study environments, poor usage of mathematical language as a tool for communication among others. This paper sets to investigate the use of mathematical language as a means of communicating mathematics being a core subject and the influence it has on academic achievement at the secondary school level in Rachuonyo region of Homabay County. In particular, the study investigates the intricacies involved in teaching mathematics. For example, do teachers use technical terms which area above the learners‟ level of understanding? The study further seeks to determine other factors related to mathematical language and how their interaction affects the performance of mathematic sat secondary school level.
http://www.ijmra.us
Keywords: Mathematical language; Secondary schools; Academic achievement